Mid-Cretaceous pCO(2) based on stomata of the extinct conifer Pseudofrenelopsis (Cheirolepidiaceae) - Haworth, M; Hesselbo, S; McElwain, J; Robinson, SA; Brunt, J (2005)
Stomatal characteristics of an extinct Cretaceous conifer, Pseudofrenelopsis parceramosa (Fontaine) Watson, are used to reconstruct atmospheric carbon dioxide (pCO2) over a time previously inferred to exhibit major fluctuations in this greenhouse gas. Samples are from nonmarine to marine strata of the Wealden and Lower Greensand Groups of England and the Potomac Group of the eastern United States, of Hauterivian to Albian age (136-100 Ma). Atmospheric pCO2 is estimated from the ratios between stomatal indices of fossil cuticles and those from four modern analogs (nearest living equivalent plants). Using this approach, and two calibration methods to explore ranges, results show relatively low and only slightly varying pCO2 over the Hauterivian-Albian interval: a low of ∼560-960 ppm in the early Barremian and a high of ∼620-1200 ppm in the Albian. Data from the Barremian Wealden Group yield pCO2 values indistinguishable from a soil-carbonate-based estimate from the same beds. The new pCO2 estimates are compatible with sedimentological and oxygen-isotope evidence for relatively cool mid-Cretaceous climates. © 2005 Geological Society of America.